A FRAMEWORK FOR GOVERNANCE IN PROJECT MANAGEMENT IN SOUTH AFRICA - Maharaj, Kiren (My University, 2011)
In the context of predicted positive economic growth in South for the next three years, the economic landscape will be characterised by a growth in investment in South Africa. Some of the investment will be underpinned by the infrastructure developments by state owned enterprises such as Eskom and Transnet. These infrastructure investments will comprise the recommissioning and construction of new power plants and investments in harbours and rail infrastructure and will be executed through projects. To access the funding required for these projects South African entities may find themselves competing for investor funding. Investor confidence will be an important criterion to access funding and credible corporate governance arrangements based on internationally accepted principles will improve access to global capital markets. Organisations will have to provide assurance that project activities are carried out on the basis of good governance so that the outcomes of projects contribute to sustainable performance and ultimately economic growth. This report examines the key governance principles that should be incorporated into the project lifecycle based on examining key literature sources in the areas of governance and project management. The outcome of this report is a framework which South African corporations can utilise to determine the governance structure and governance practices that apply to a project environment within the context of broader corporate governance
MBA thesis - WBS
Keywords: Project management; Corporate governance